Methylphenidate-Induced Raynaud’s Phenomenon In Two Cases With Attention-Deficit/Hyperactivity Disorder - Ömer Faruk Akça; Hurşit Ferahkaya (Journal of Contemporary Medicine, 2021)
Attention-deficit/hyperactivity disorder is a common neurodevelopmental disorder in childhood, for which there are several different treatment options. Among the suggested medications, methylphenidate (a central nervous system stimulant) is the first option in the treatment of ADHD. Psychostimulants are associated with various vascular problems including peripheral vasculopathy. This report describes two patients with ADHD who developed Raynaud's phenomenon during the modified-release methylphenidate treatment.